Elastic strain tensor of zirconium hydrides in Zr2.5%Nb pressure tubes by synchrotron X‐ray diffraction. Issue 5 (20th September 2019) - Vicente Alvarez, Miguel Angel; Santisteban, Javier; Domizzi, Gladys; Okasinski, John; Almer, Jonathan
Abstract : Knowing the stress/strain state of hydrides is important to understand the stress‐induced degradation mechanisms of components made of zirconium alloys. X‐ray diffraction is used to evaluate such a strain state through a novel approach based on the interpretation of strain pole figures. Abstract : Zirconium alloys are used in fuel cladding and structural components of nuclear power plants. Hydrogen enters the Zr matrix during plant operation and precipitates as hydride particles that degrade the mechanical properties of the alloy, limiting service life. Knowledge of the stress state within hydride precipitates is important to understand stress‐induced degradation mechanisms such as delayed hydride cracking, but no direct quantification has yet been reported in the literature. Here, measurements are reported of the average elastic strain tensor within δ zirconium hydride precipitates in Zr2.5%Nb pressure tube material from CANDU power plants. Complete intensity and strain pole figures for the hydride were obtained by synchrotron X‐ray diffraction experiments on specimens with hydrogen contents ranging from ∼100 wt p.p.m. hydrogen to nearly 100% δ‐hydride. Zirconium hydride precipitates by a process involving a martensitic transformation, with two hydride variants possible from a single α‐Zr grain. A synthetic model of the hydride crystallographic texture allowed the interpretation of the measured strain pole figures and quantification of the elastic strain tensor for both texture components. It was found that the two variants appear in nearly equal proportion but with different stress states, differing in the sign of the shear strain components (∼±3000 µϵ). This difference is possibly associated with the shear movement of Zr atoms during the phase transformation. This suggests that hydride clusters are composed of stacks of smaller hydrides in alternating hydride variants. Stresses were estimated from a set of rather uncertain hydride elastic constants. Overall, both variants showed compressive strains along the tube axial direction (∼5000 µϵ). For low hydrogen concentrations, the hydrides' stress tensor is dominated by compressive stresses of ∼300 MPa along the axial direction, probably caused by the elongated morphology of hydride clusters along this direction, and variant‐dependent shear stresses of ∼±100 MPa, probably from the shear movement of the Zr atoms involved in the phase transformation.